The Effects of Shear on Mode II Delamination: A Critical Review (Fracture and Structural Integrity, 2018)
The paper focuses on the effects of shear deformation and shear forces on the mode II contribution to the energy release rate in delaminated beams. A critical review of the relevant literature is presented, starting from the end-notched flexure test as the prototype of delaminated laminates subjected to pure mode II fracture. Several models of the literature are recalled from simple beam theory to more refined models. The role of first-order shear deformation in line with the Timoshenko beam theory is investigated as distinct from the local crack-tip deformation related to the shear modulus of the material. Then, attention is moved on to a general delaminated beam with an arbitrarily located through-the-width delamination, subjected to mixed-mode fracture. Several fracture mode partition methods of the literature are reviewed with specific attention on the effects of shear forces and shear deformation on the mode II contribution to the energy release rate.
Keywords: Delamination; Mixed-mode fracture; Mode II fracture; Beam theory; Shear deformation; End-notched flexure test